Cancer risk perceptions and distress among women attending a familial ovarian cancer clinic - Cull, A (Nature Publishing Group, 2001)
Of 230 women referred to a familial ovarian cancer clinic, 196 (85%) completed a questionnaire before they attended. The data collected included pre-counselling risk perceptions and an assessment of distress. Respondents were more likely to underestimate (44%) than overestimate (19%) their risk. Those with a family history of breast and ovarian cancer (HBOC) were particularly likely to underestimate their ovarian cancer risk. The variables assessed in this study – sociodemographic, family history, distress, anxiety proneness, coping style and beliefs about health control – explained little of the observed variation in accuracy of risk perception. On the General Health Questionnaire (GHQ-30) 30% of the sample obtained scores above the cut-off (≥ 6) recommended for screening for ‘case-level’ psychological distress. Women exhibiting case-level distress were more likely to overestimate their risk (OR = 2.3). On univariate analysis low internal locus of control was associated with ‘case-level’ distress (P = 0.008). On multiple regression the best predictors of ‘caseness’ were high-trait anxiety, being a graduate and inaccurate risk perception. There was no difference in the level of distress shown by women with HBOC vs. those with a history of ovarian cancer only. Implications of these findings for the counselling needs of the women are discussed. The effectiveness of the clinic in improving the accuracy of risk perceptions and relieving distress is being assessed. © 2001 Cancer Research Campaign http://www.bjcancer.com